Training on behaviour management for promoting effective teaching-learning: A case of Dakawa and Morogoro teacher colleges in Tanzania - Mkilindi, Stella Z. (Mzumbe University, 2024)
The purpose of this study was to assess the training on behaviour management for promoting effective teaching-learning done at Morogoro, it based on examining the contents of training on behaviour management offered and identifying different approaches of behaviour management taught to pre-service teachers. The study also explored the challenges encountered in training on behaviour management and investigated the application of behaviour management skills in effective teaching and learning at Dakawa and Morogoro teachers training colleges. The intent of the study was to contribute to the overall knowledge base about the training of pre-service teachers on behaviour management approaches regarding learner‟s behavioral conditions. Specifically, this study focuses on preparation of the pre-service teachers on behaviour management before they commence teaching-learning job. The study drew a sample of 97 respondents who were got through purposive and random sampling, the approach was mixed but due to the nature and purpose of the study qualitative study dominated, the framework designed was multiple case studies, data were obtained through questionnaires, interview, and semi structured interviews as well as focused group discussion and analyzed through descriptive statistics with the help of students package for social sciences (SPSS), tables presented the data in frequency and percentage from the scale of yes/no. The study found that pre service teachers were trained on behaviour management basing on theories such as social learning, connectionism, skinners and Jean Piaget theories whereas the models/approaches were found and concluded that, there is the relationship between training on behaviour management in promoting effective teaching-learning at Morogoro region in Tanzania. Greater emphasis should be placed on preparing both general and special educators to be competent and efficient at managing today‟s classrooms with their diverse range of learners.